Expression of tumor suppressive microRNA‐34a is associated with a reduced risk of bladder cancer recurrence. Issue 5 (25th February 2015) - Andrew, Angeline S.; Marsit, Carmen J.; Schned, Alan R.; Seigne, John D.; Kelsey, Karl T.; Moore, Jason H.; Perreard, Laurent; Karagas, Margaret R.; Sempere, Lorenzo F.
<x xml:space="preserve">Abstract</x> Bladder cancer is the fourth most common cancer among men in the United States and more than half of patients experience recurrences within 5 years after initial diagnosis. Additional clinically informative and actionable biomarkers of the recurrent bladder cancer phenotypes are needed to improve screening and molecular therapeutic approaches for recurrence prevention. MicroRNA‐34a (miR‐34a) is a short noncoding regulatory RNA with tumor suppressive attributes. We leveraged our unique, large, population‐based prognostic study of bladder cancer in New Hampshire, United States to evaluate miR‐34a expression levels in individual tumor cells to assess prognostic value. We collected detailed exposure and medical history data, as well as tumor tissue specimens from bladder patients and followed them long‐term for recurrence, progression and survival. Fluorescence‐based in situ hybridization assays were performed on urothelial carcinoma tissue specimens (n = 229). A larger proportion of the nonmuscle invasive tumors had high levels of miR‐34a within the carcinoma cells compared to those tumors that were muscle invasive. Patients with high miR‐34a levels in their baseline nonmuscle invasive tumors experienced lower risks of recurrence (adjusted hazard ratio 0.57, 95% confidence interval 0.34–0.93). Consistent with these observations, we demonstrated a functional tumor suppressive role for miR‐34a in cultured urothelial cells, including reduced matrigel invasion and growth in soft agar. Our results highlight the need for further clinical studies of miR‐34a as a guide for recurrence screening and as a possible candidate therapeutic target in the bladder.